Meta Analysis: Effects of Family Support, Family Income, and Domestic Violence on Postpartum Depression - Mulyani, Noris Hadi Sri; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Postpartum depression is a form of depression that occurs during the puerperium with specific symptoms that appear 4-6 weeks after delivery and can last for months, affecting the happiness and emotional relationship between mother and child. This study aims to analyze the effect and estimate the size of the effect of family support, family income levels and domestic violence on the incidence of depression among postpartum women with a meta-analysis. Subject and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: postpartum mothers. Intervention: strong family support, high family income levels and domestic violence. Comparison: weak family support, low family income level and no domestic violence. Outcome: postpartum depression. The online databases used are Google Scholar, Hindawi, PubMed, Science Direct, Scopus, and ResearchGate. There were 18 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: Meta-analysis of 18 articles with cross-sectional research designs from different countries, with a sample size of 29,638 research subjects. The results of the meta-analysis show that there is an effect of family support on the risk of postpartum depression. Mothers who received high family support had a risk of experiencing postpartum depression by 0.69 times lower compared to those who received low family support (aOR= 0.69; 95% CI= 0.38 to 1.27; p=0.240). Mothers with high family income levels have a risk of experiencing postpartum depression by 0.50 times lower compared to low family income levels (aOR= 0.50; 95% CI= 0.28 to 0.90; p=0.020). Mothers who experience domestic violence have a risk of postpartum depression by 4.20 times higher compared to those who do not experience domestic violence and the relationship is statistically significant (aOR=4.20; CI 95% =2.56 hingga 6.88; p<0.001). Conclusion: Strong family support and high levels of family income reduce the risk of postpartum depression. Meanwhile, domestic violence increases the risk of postpartum depression. Keywords: Postpartum Depression, Family suport, Family income, Domestic violence. Correspondence: Noris Hadi Sri Mulyani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: hadinoris@gmail.com. Mobile: 08157996639